A plan of implementation for the Denver occupational adjustment service - Miller, Graham R., author; Hinderman, Roy Aaron, 1900-, advisor; Avery, George T., committee member; Wetzel, Clarence Ludwig, committee member; Craigo, R. T., committee member; Brayfield, Arthur H., committee member; Betts, Gilbert L., committee member (Colorado State University. Libraries, 1941)
To view the abstract, please see the full text of the document.
Keywords: Denver (Colo.) -- Occupations; Vocational education -- Colorado -- Denver; Educational counseling; School attendance -- Colorado -- Denver